Cancer in XXI century - Solidoro Santisteban, Andrés (2006)
Most common cancers in developing World-stomach, cervix, lung and liver cancer have decreased in incidence and mortality in industrialized countries, but remain as a serious public health problem in our country. Disparities in cancer are caused by the complex interplay of low economic class, culture and social injustice with poverty playing the dominant role. These areas should be delineated and targeted with an intense approach to provide education, appropriate access to screening, diagnosis, treatment and an improved social support.